Diseño y construcción de máquina dispensadora automática de materiales de escritorio mediante el uso de la plataforma Arduino - Arévalo Chalacán, Edwin Gabriel (2018)
The design of a desktop vending machine is an innovative idea in a low-key environment. This document explains the implementation of this project. Where the needs of the user and a new scheme of fast and safe sale became the bases of creation of the team. In the first stage of the project, it was researched about the different types of dispensing machines, their market, types of products to be dispensed and the most forms of automation. It avoids the vandalism, significant risks that runs this type of equipment. In the second stage, an analysis and selection of alternatives concerning the design and construction of the dispensing machine was established. In terms of the automation system, design and operation of the mechanism and protection of the machine. The materials and alternatives selected, join to the affordability in the Ecuadorian market and its ease of manufacturing. The third stage, involves programming on the Arduino MEGA platform, in order to operate the main mechanism of the machine and other electronic components. In addition, design calculations were obtained regarding to the total weight of the modules, resistance criteria, maximum bending stress, surface adjustments, dimensions of the machine components, calculations that were corroborated by the SolidWorks software. The manufacture of the reinforcement, casing, plate-beam, hopper and the dispensing mechanism was carried out by workshop-assisted process planning. The final stage corresponds to the start-up of the machine, where data was obtained that shows us which product had higher sales, as well as the vulnerable points of the machine.